CHARACTERIZATION OF SORPTION MATERIALS CONTAINING OXIDES OF MULTIVALENT METALS FOR USE IN PROCESSES OF LITHIUM EXTRACTION FROM SALT SOLUTIONS - Chaban, M. A.; Pal’chik, A. V.; Rozhdestvenskaya, L. M.; Vasilyuk, S. L.; Linkov, V. M. (Water and Water Purification Technologies. Scientific and Technical News, 2016)
Since lithium is one of the most popular materials for the electronics industry, it is of interest to consider alternative sources of its receipt. The article analyzes the main sources of lithium production, global stocks and the dynamics of its production. We have considered the possibility of obtaining lithium from sea water by sorption method. The comparative characteristic of sorption materials based on the multivalent metal oxides was conducted, their structure parameters were determined. By method of X-ray analysis structure of the sorbents was studied. It is shown that the titanium-manganese sorbent is composite material consisting of particles of TiO2, rutile coated with amorphous MnO2. By electron paramagnetic resonance method valence states of manganese component in the sorbent structure were set. Adsorption isotherms from lithium solutions simulating sea water were obtained. The effect of modification of sorption materials by ion application was studied. It is shown that the highest sorption capacity to Li+ ions corresponds to titanium-manganese sorbent.